Revelation's hymns commentary on the cosmic conflict - Grabiner, Steven Charles ([London] : Bloomsbury T&T Clark, 2015)
"Revelation's Hymns examines the hymnic pericopes in Revelation in light of the cosmic conflict theme. It considers this theme as integral to the development of Revelation's plot. Recognizing that critical studies give interpretative primacy to the political realities that existed at the time of Revelation's composition, Grabiner responds to the need for an examination of the storyline from the perspective of issues that are of narrative importance. Grabiner argues that the cosmic conflict is at the centre of the book's concerns, and attempts to determine the function of the hymns with respect to this. Previous examinations of the hymns have considered them as a response and/or parody to Roman liturgy, examples of God's unquestioned sovereignty, or expressions of thematic overtones found throughout the book. While these approaches make a contribution to a greater understanding of the hymns, the relation to the ever-present conflict theme has not been explored. This study allows the hymnic sections to engage with the larger narrative issue as to who is truly the rightful sovereign of the universe. "--Bloomsbury Publishing.
Includes bibliographical references and index.
Also issued in print.
Electronic reproduction.
Keywords: Bible. -- Commentaries; Hymns in the Bible